2020
DOI: 10.1111/jop.13095
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucosal lesions in psoriatic patients based on disease severity and treatment approach

Abstract: Background This observational case‐control study was designed to investigate the frequency of oral lesions in psoriatic patients and to identify an association between mucosal involvement, the severity of the disease, and a form of treatment. Methods One hundred twenty‐seven patients diagnosed with psoriasis were enrolled in this study from November 2018 to September 2019. The oral mucosa evaluation was based on the clinical appearance, location, and morphology of the lesions. All patients completed a general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…The PASI score was statistically higher in patients affected by GT, and exhibited less improvement after treatment (204). However a prospective case-control study in an Austrian cohort found that psoriasis was associated with fissured tongue but not with GT (207), and the severity of the disease evaluated by the PASI scale did not influence mucosal involvement (208).…”
Section: Oral Comorbidities Geographic Tonguementioning
confidence: 89%
“…The PASI score was statistically higher in patients affected by GT, and exhibited less improvement after treatment (204). However a prospective case-control study in an Austrian cohort found that psoriasis was associated with fissured tongue but not with GT (207), and the severity of the disease evaluated by the PASI scale did not influence mucosal involvement (208).…”
Section: Oral Comorbidities Geographic Tonguementioning
confidence: 89%
“…The oral mucosal lesions associated with psoriasis are mainly limited to the tongue 27,28 . Costa et al .…”
Section: Discussionmentioning
confidence: 99%
“…The oral mucosal lesions associated with psoriasis are mainly limited to the tongue. Fissured tongue described as the presence of anteroposteriorly or laterally oriented fissures on the dorsal surface of the tongue affects 2-5% of the general population and seems to be the most common oral lesion in psoriatic patients [26][27][28][29] The geographic tongue, characterized as well-demarcated zones of erythema at dorsal tongue mucosa, because it is associated with increased levels of TNF-a and IL-6, occurs less frequently in a population managed with biologicals [26,30].…”
Section: Discussionmentioning
confidence: 99%